Promoting responsible sovereign lending and borrowing: the role of sovereign wealth funds. Issue 4 (11th November 2019) - Pavlidis, Georgios
Abstract : Purpose: This paper aims to investigate the idea of building responsible borrowing and lending into sovereign wealth fund (SWF) decision-making. SWFs, which currently manage US8 trillion in assets, are influential institutional investors, but their role in sovereign debt markets needs to be further explored. In this context, this paper aims to critically assess the linkages and convergences between the Santiago Principles on SWF and the United Nations Conference on Trade and Development (UNCTAD) principles on responsible sovereign lending and borrowing. Design/methodology/approach: This paper draws on legal scholarship, reports, policy papers and other open-source data to explore the role of SWFs in sovereign lending, borrowing and debt restructuring. Findings: Building responsible borrowing and lending into SWF decision-making is feasible and justified on the grounds of both ethics and public duty. It is also justified in financial terms because it would protect SWFs from irresponsible lending and borrowing practices at the micro level while contributing to global financial stability at the macro level. Originality/value: This is the first comprehensive study to juxtapose two important normative processes, the Santiago Principles and the UNCTAD Principles.